2013
DOI: 10.1590/s1517-83822014005000011
|View full text |Cite
|
Sign up to set email alerts
|

Anti dermatophytic therapy: prospects for the discovery of new drugs from natural products

Abstract: Millions of people and animals suffer from superficial infections caused by a group of highly specialized filamentous fungi, the dermatophytes, which only infect keratinized structures. With the appearance of AIDS, the incidence of dermatophytosis has increased. Current drug therapy used for these infections is often toxic, long-term, and expensive and has limited effectiveness; therefore, the discovery of new anti dermatophytic compounds is a necessity. Natural products have been the most productive source fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
0
23
0
1
Order By: Relevance
“…Besides the prevalence of resistance of dermatophytes, many synthetic antifungal drugs had also been associated with some adverse side effects such as hepatotoxicity, nausea, diarrhoea and impotency (Del Palacio et al 2000). This occurs as result of cellular similarities between the fungi and mammalian, which make the treatment of dermatophyte infections to be tedious, expensive and time consuming (Soares et al 2013). Hence, there is a need to provide affordable and appropriate treatment for dermatophyte infections without side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the prevalence of resistance of dermatophytes, many synthetic antifungal drugs had also been associated with some adverse side effects such as hepatotoxicity, nausea, diarrhoea and impotency (Del Palacio et al 2000). This occurs as result of cellular similarities between the fungi and mammalian, which make the treatment of dermatophyte infections to be tedious, expensive and time consuming (Soares et al 2013). Hence, there is a need to provide affordable and appropriate treatment for dermatophyte infections without side effects.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports about development of resistance to antifungal drugs, 25 especially in the group of azoles 4 and against terbinafine. 26 It has been suggested that T. rubrum may become resistant to terbinafine due to missense mutation in the squalene epoxidase gene leading an amino acid substitution. 27 Recent efforts in dermatophyte genome sequencing and transcriptome and proteome analysis provide information to develop new specific drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several studies have been conducted to explore new active substances as an alternative to the conventional therapy or its complementation . Like a multitarget approach, the combination therapy has been used as a strategy for the lack of new antimicrobial drugs .…”
Section: Introductionmentioning
confidence: 99%
“…[4] In this context, several studies have been conducted to explore new active substances as an alternative to the conventional therapy or its complementation. [5,6] Like a multitarget approach, the combination therapy has been used as a strategy for the lack of new antimicrobial drugs. [7,8] Therefore, the identification of synergistic associations has been the focus of several studies evaluating antifungal combination therapies.…”
Section: Introductionmentioning
confidence: 99%